2016
DOI: 10.1002/cam4.841
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the relationship between metastases and cachexia in lung cancer patients

Abstract: Weight loss and hematogenous metastases are poor prognosis factors in lung cancer patients that can but do not necessarily co‐occur. We retrospectively investigated the clinical association between cachexia, tumor characteristics (such as metastatic burden and mutational status), and treatment in lung cancer patients. The medical records of 394 lung cancer patients from two institutions (Columbia University, USA and Tohoku University, Japan) were reviewed. Information collected included the presence of cachexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
0
29
0
1
Order By: Relevance
“…IL‐6 and TNF‐α are important multifunctional cytokines involved in tumour growth and metastasis. A retrospective clinical study of lung cancer patients found a possible link between metastasis and cachexia that was associated with the inherent tumour characteristics …”
Section: Discussionmentioning
confidence: 99%
“…IL‐6 and TNF‐α are important multifunctional cytokines involved in tumour growth and metastasis. A retrospective clinical study of lung cancer patients found a possible link between metastasis and cachexia that was associated with the inherent tumour characteristics …”
Section: Discussionmentioning
confidence: 99%
“…KRAS mutations are related to drivers linked to aggressiveness in cancer and, consequently, correlate with poor prognosis. A recent study showed that MAPK signalling is constitutively active in KRAS‐mutated colorectal cancer, and other studies have shown that tumours with mutated KRAS were associated with an increased risk of weight loss . Unfortunately, we did not examine tumour genetic profile; hence, we cannot discard an interference of this parameter in our results.…”
Section: Discussionmentioning
confidence: 92%
“…. On the other hand, several studies show that the presence of cachexia is not directly or exclusively related to greater tumour burden and/or with metastasis; nonetheless, it has been recently shown that metastatic cancer is associated with a higher risk for concomitant cachexia …”
Section: Introductionmentioning
confidence: 99%
“…The progression of cachexia is exacerbated in the presence of metastasis. For example, in lung cancer patients with metastasis, occurrence of cachexia is higher in metastatic patients than in nonmetastatic patients . As with sarcopenia, cachexia is not limited to those with a BMI <25.…”
Section: Muscle Loss In Cancer Patientsmentioning
confidence: 99%